Effects of Reduced Amino Acids and Apparent Metabolizable Energy on Meat Processing, Internal Organ Development, and Economic Returns of Cobb 700 and Ross 708 Broilers - Bo Zhang; Shengyu Zhou; Wei Zhai; Yang Zhao (Animals)
The rapid growth and high nutrient density in modern broiler production have led to issues like woody breast myopathy (WBM), footpad dermatitis, and fat accumulation, affecting welfare and profitability. This study evaluated the effects of amino acid (AA) and apparent metabolizable energy (AME) reductions on organ development, carcass yield, WBM incidence, and economic returns in Cobb 700 and Ross 708 broilers. Two trials were conducted, one per strain, using a factorial design with 12 treatments (four AA × three AME). Each trial included 864 broilers, randomly assigned to six replicate blocks, with 12 pens per block (six males and six females per pen). Diets contained 70%, 80%, 90%, or 100% of digestible AA and 84%, 92%, or 100% AME based on breeder recommendations. A 30% AA reduction increased fat pad weight, promoted proventriculus and jejunum development (day 58), reduced carcass and tenderloin weights, lowered moderate/severe WBM incidence (day 47), and shortened footpad dermatitis. A 16% AME reduction decreased fat pad weight, improved muscle production and returns, but reduced normal breast percentage (days 40 and 47). The recommended protein–energy ratio (g/MJ) for optimal economic returns was as follows: 19.78 (0–10 d), 17.51 (11–24 d), 16.03 (25–39 d), and 15.25 (40–63 d).